1996
DOI: 10.1021/la950821v
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Air−Water Interfacial Area in Wet “Unsaturated” Porous Media

Abstract: A method is proposed for determining the area of the air−water interface in wet but unsaturated porous media. The method depends on determining the critical concentration of surfactant necessary to achieve water movement within the system. Effective surfactants are insoluble in water, are spread as monolayers at the air−water interface, and form solid monolayers which have little or no effect on the surface tension of water until surface concentration of surfactant molecules reaches a known critical value. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 7 publications
4
68
1
Order By: Relevance
“…These techniques are mostly categorized under two main groups; tracers or imaging techniques. Aqueous tracers have been used by Karkare and Fort (1996), Brusseau et al (1997), Kim et al (1997), Saripalli et al (1998), Anwar (2000), Schaefer et al (2000), and Chen and Kibbey (2006), and gas tracers have been used in some other studies such as Kim et al (1999), Costanza-Robinson and Brusseau (2002), and Brusseau et al (2006). Imaging techniques have been used by Montemagno and Gray (1995), Wildenschild et al (2002), Cheng et al (2004), Culligan et al (2004), Al-Raoush and Willson (2005a,b), and Brusseau (2005, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are mostly categorized under two main groups; tracers or imaging techniques. Aqueous tracers have been used by Karkare and Fort (1996), Brusseau et al (1997), Kim et al (1997), Saripalli et al (1998), Anwar (2000), Schaefer et al (2000), and Chen and Kibbey (2006), and gas tracers have been used in some other studies such as Kim et al (1999), Costanza-Robinson and Brusseau (2002), and Brusseau et al (2006). Imaging techniques have been used by Montemagno and Gray (1995), Wildenschild et al (2002), Cheng et al (2004), Culligan et al (2004), Al-Raoush and Willson (2005a,b), and Brusseau (2005, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, further studies performed by Henry et al 4 found that the resultant moisture content distribution in the column was different when the low-solubility alcohol as butanol was used. In the literature, sand was almost always used to simulate the wet unsaturated porous medium, 1,[5][6][7][8][9][10] and similar results indicate that the surfactant causes differences in capillary pressure within the system and water moves to re-establish equilibrium. [7][8] The amount of water that moves depends 7 on all the factors that influence capillary pressure -particle wettability, size, size distribution, packing, etc., as well as the character of the surfactant monolayer that establishes the capillary pressure gradient within the system.…”
Section: Introductionmentioning
confidence: 92%
“…A recent surge in interest in this topic, however, has led to several potentially viable approaches. Static column methods based on the use of water-insoluble surfactants have recently been proposed as a means to measure interfacial areas (42)(43)(44)(45). In addition, experimental methods based on visualization techniques have been proposed (e.g., 46).…”
Section: Fluid-fluid Interfacial Areasmentioning
confidence: 99%